Fungal endophytes in halophytic populations of Festuca rubra subsp. litoralis - Zabalgogeazcoa, Iñigo; Vázquez de Aldana, Beatriz R.; García Ciudad, Antonia; García Criado, Balbino (2000)
Resumen del trabajo presentado en el 4th International Neotyphodium/Grass Interactions Symposium, celebrado en Soest (Alemania), del 27 al 29 de septiembre de 2000 Festuca rubra subsp. litoralis is a grass adapted to very unhospitable environments. In sea cliffs of the North Atlantic coast of Spain,this species occupies the frrst line of vegetation with other halophytes such as Armeria maritima. These plants are exposed to winds, salt water spray, and grow in almost no soil. Several sea cHff populations of F. rubra litoralis have been studied. Sorne plants are infected by an asymptornatic endophyte. The fungus has Neotyphodium morphology, and it is vertically transmitted by seed. The presence of ergovaline has been detected in infected p)ants. The high frequencies of endophytic infection observed in sorne popu)ations (i.e. 70%) suggests that endophytic infection is not deleterious to plants growing in this harsh environment.